Pest categorisation of Anisogramma anomala. (22nd February 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health (PLH) Panel performed a pest categorisation of Anisogramma anomala, a well‐defined and distinguishable fungal species of the family Valsaceae. The pathogen is regulated in Annex IIAI of Council Directive 2000/29/EC as a harmful organism whose introduction into the EU is banned on plants of Corylus L., intended for planting, other than seeds, originating in Canada and the USA. The fungus is native to eastern North America and causes eastern filbert blight on cultivated hazel, Corylus avellana, as well as on wild hazel ( Corylus spp.). In the 1960s, the disease spread on infected plant material to Oregon, where it then threatened US hazelnut production in the Willamette Valley. The pest could enter the EU via plants for planting. Hosts and favourable climatic conditions are common in the EU, thus facilitating establishment. The pest would be able to spread following establishment through infected plants for planting and ascospore dispersal. A. anomala leads to canopy and yield loss and can cause death of Corylus trees. Should the pathogen be introduced into the EU, impacts can be expected not just on hazel as a crop and as an ornamental but also in coppices and woodlands, where Corylus species provide an important habitat. In Oregon, scouting for cankers, therapeutic pruning and copious fungicide applications are reported to be necessary (but costly measures) to continue hazelnut production in the presence of the disease. Breeding for resistance led to the selection of resistant cultivars. The main knowledge gaps concern (i) the role of deadwood and cut branches as potential entry pathways and means of spread and (ii) the susceptibility of C. avellana cultivars and of Corylus spp. in the wild in the EU. The criteria assessed by the Panel for consideration as a potential quarantine pest are met. For regulated non‐quarantine pests, the criterion on the pest presence in the EU is not met.